Systemic atrioventricular valve replacement due to a supravalvular stenosing ring and ebsteinoid tricuspid valve in a patient with congenitally corrected transposition of the great arteries: a case report - Zacarías Mendoza, Nathalie Victoria (2025)
Congenitally corrected transposition of the great arteries (ccTGA) is a rare and complex cardiac malformation often associated with additional anomalies. We present a 23-year-old patient with ccTGA, a supravalvular stenosing ring, and an Ebsteinoid tricuspid valve who developed severe systemic atrioventricular valve (SAVV) stenosis and regurgitation. Preoperative evaluation revealed tricuspid valve abnormalities, a dilated systemic right ventricle (sRV) with a reduced sRV ejection fraction (42%). The patient underwent bioprosthetic SAVV replacement and excision of the supravalvular membrane. Postoperatively, valve function was preserved, and recovery was favorable despite transient complications. This case emphasizes the surgical challenges and individualized decisionmaking required in ccTGA with rare anatomical variants, highlighting the value of timely intervention, multidisciplinary care, and long-term follow-up to optimize outcomes.